Effect of Cold Work on the Precipitation Process in Aluminum Alloy 6063 - Fettah, Sheirko Shakir; Mahmood, Omer Salih; RojbeYani, Shawnim R. Jalal (Sulaimani Journal for Pure and Applied Sciences, 2007)
Aluminum alloys can be strengthetred by cold or hot working due to interaction between precipitates and dislocations. The alloy 6063-was deformed (2, 5, 10, f S,an{-ZO) oh aftet water quenching' and artificially aged at different aging temperatures (16b, 180 and 200) oC for various periods of time (0'5' 5' 10, 50 and 100) hours. The risults showed a considerable improvement in yield and tensile strength with an increasing level of prestrain. Generally aging temperature of 160 oC gave the best- in^crease of yield and tensile strength, but these were decreasia *itt incieasing aging temperature i'e' (180 and 200) "C at a given level of presh'ain. -r --.:.L ^- :-^-^- " Th" peak aging time that improves the mechanical properties decreased with an increasing aging temperature. The alloy of 20 Yadeformation anJageO at tOO iC for l0 hours developed maximum (yield' tensile strength and hardness) values .o*pur"d rriih all other conditions involved, because the density of dislocation tangles which improved (yield and tensile) strength increased with increasing degree of prestrain. The 6xxx aluminum alloYs are local softening in the heat-affected parent metal.
Keywords: cold work; precipitation; 6063; mechanical properties